Tribulus Terrestris L Extract Effects on Slow Down Ageing Process (Central Asian Journal of Medical Sciences, 2021)
Objective: Tribulus Terrestris is a medicinal plant cultivated in temperate regions of the world. Inner Mongolia is one of the main producing areas of Tribulus Terrestris. We aimed in this study to examine the effect of Tribulus Terrestris extract on the aging process. Methods: A total of 50 mice were used for the experiment. They were divided randomly into 5 groups (10 animals in each group): normal control group and four aging groups. Results: Compared to the normal aging group, the parameters of the thymus gland and spleen of an aging group fed with a high and medium amount of Tribulus has visibly increased (p < 0.05). The content of blood catalase (CAT) and superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) of blood serum of an aging group fed with a high and medium amount of Tribulus Terrestris has visibly increased (p < 0.05) compared to that in the aging group. Also, the content of malondialdehyde (MDA) in blood serum has visibly lowered. We further have measured the SOD, GSH-Px content in brain tissue of each group of mice. Conclusion: Compared with the normal control group, the SOD content was decreased significantly and MDA content was significantly increased in the aging group of mice.